Multislice CT angiography in the assessment of coronary artery in-stent restenosis: A systematic review. - Sun, Zhonghua; Davidson, R.; Lin, C. (Elsevier, 2008)
Purpose: The aim of this study was to perform a systematic review of the diagnostic accuracy of multi-detector row computed tomography angiography (MDCT) for detection of coronary in-stent restenosis in patients treated with coronary stenting when compared to invasive catheter angiography.Materials and Methods: A search of PUBMED and MEDLINE databases for English literature was performed. Only studies with at least 10 patients comparing 16- or more detector rows MDCT angiography with invasive catheter angiography in the detection of coronary in-stent restenosis (more than 50% stenosis) were included for analysis. Sensitivity and specificity estimates pooled across studies were tested using a fixed effects model.Results: 15 studies met selection criteria for inclusion in the analysis. There were eight studies performed with 16-detector row CT scanners, and five studies with 64-detector row scanners and one study with a 40-detector scanner. The remaining study was performed with a mixture of 16-and 64-detector row scanners. Prevalence of in-stent restenosis following coronary stenting was 18% (95% CI: 13%, 24%). Pooled estimates of the sensitivity and specificity of overall MDCT angiography for the detection of coronary in-stent restenosis was 85% (95% CI: 78%, 90%) and 97% (95% CI: 95%, 98%), respectively. No significant difference was found between 16- and 64-detector row scanners regarding the sensitivity and specificity of MDCT for assessment of in-stent restenosis (p>0.05).Conclusion: The results showed that MDCT angiography (with 16 or more detector rows) has moderate sensitivity and high specificity for the detection of coronary in-stent restenosis when compared to invasive catheter angiography. A high specificity value of MDCT may be most valuable as a non-invasive technique of excluding coronary stent restenosis or occlusion. The main factors affecting visualization are stent diameters and stent materials.